Expression of concern - Agudelo-Suárez, Andres Alonso (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Expression of concern about the article "The learning environment at a public university in Northern Chile: How is dental education perceived by students?" (DOI: http://dx.doi.org/10.17533/udea.rfo.v29n1a2) by José Pablo Tisi Lanchares, Luis Barrios Piñeiro, Ismael Henríquez Gutiérrez, and Gerardo Durán Ojeda.